Pembuatan peralatan two in one (hand sanitizer dan hand dryer otomatis) - Prantasi Harmi Tjahjanti; Ali Akbar; Rachmat Firdaus; Alfiansyah Satrio Wicaksono; Mohammad Afif Fajar; Ajitiyo Dananjoyo (University of Muhammadiyah Jakarta, 2022)
The development of the Corona virus or COVID-19 in Indonesia is still developing until now. The best way of prevention to avoid the factors that can cause this viral infection, one of which is routine hand washing with soap and water or hand sanitizer. The problem is hand sanitizer that exist now always using hand power to squeeze or spray them like holding/pressing, we can think if this hand sanitizer is for the public, how many hundred hands of different people will hold it, and of course this actually causes infected with the Corona virus. Aim of the study is make two in one equipment (hand sanitizer and handdryer automatic), which means that the equipment can be used for hand sanitizer without having to hold/press/squeeze the hand sanitizer and also have the dryer. The results obtained when the fingers are closer to the hand sanitizer, it will release the liquid in ± 3 seconds, and if the liquid is a gel it will come out in about ± 5 seconds. For the handdryer, it takes ± 2 seconds to remove the hot air.